"Well-Behaved Robots Rarely Make History": Coactive Technologies and Partner Relations. (4th May 2018) - Skågeby, Jörgen
Abstract: Technologies equipped with artificial intelligence and an agency of their own are becoming increasingly available to consumers. Rather than just augmenting human senses or mediating information, these coactive technologies are mobile, pro-active, context-sensitive, programmable, and agential in the milieu of the user. This paper illustrates a humanistic human–computer interaction (HCI) approach to coactive technologies by analyzing the artificial intelligence (AI) powered robot Cozmo. The analysis demonstrates how Cozmo: 1) remediates fictional characteristics to appear more familiar, emotional, and lovable; 2) is both pre-programmed and programmable, creating an interesting tension in its agential spectrum; and 3) is discursively marketed as a cunning, emotional, and non-machinic accomplice. Referring to established models of human–technology relations, the paper introduces the concept of partner relations, where a coactive human–machine intentionality is negotiated. The paper also discusses potential implications for designers, who must focus on the multitude of partner relations and joint intentionalities that new coactive technologies can engender.